Festival Ngejot Sebagai Arena Rekonstruksi Identitas Budaya Masyarakat Sasak - Nadia Safitri Riskinta; Ahmad Tohri; Muh. Ridwan Markarma (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
The transformation of local traditions into cultural festivals has become an important strategy for preserving cultural heritage while responding to contemporary social change. This study aims to analyze the construction of symbolic meanings in the Ngejot Festival and explain how symbolic interactions contribute to the reconstruction of the cultural identity of the Sasak community. A qualitative approach with an intrinsic case study design was employed in Lenek Village, East Lombok, Indonesia. Data were collected through participant observation, in-depth semi-structured interviews, and document analysis, and were analyzed using thematic analysis informed by Herbert Blumer's Symbolic Interactionism and Émile Durkheim's Social Solidarity Theory. The findings indicate that the Ngejot Festival has evolved from a family-based food-sharing tradition into a participatory cultural festival that strengthens community engagement, intergenerational cultural transmission, and collective identity. Cultural symbols, including dulang, topat bulayak, janur kuning, sampak, and the ngatong jot procession, function as symbolic media through which values of respect, reciprocity, cooperation, religiosity, and solidarity are collectively interpreted and reproduced. The study demonstrates that Sasak cultural identity is continuously reconstructed through symbolic interaction, collective participation, meaning negotiation, and the internalization of shared cultural values. It proposes a conceptual model positioning the Ngejot Festival as an arena for cultural identity reconstruction, offering theoretical contributions to cultural sociology and practical insights for participatory cultural heritage preservation and community-based cultural policy.